Human Capital: Essence And Role in Increasing Organization Effectiveness (Eurasian Research Bulletin, 2024)
The article examines the concept of human capital and its structural elements from the point of view of various authors. The authors studied the characteristic features of human capital that distinguish it from other types of capital. The features of the organization's human capital, methods for its assessment have been studied, and the role of human capital in increasing the organization's efficiency has been determined. It was revealed that the effectiveness of human capital management depends on the mobility of labor resources. As a result of the study, the author presented a model for managing the human capital of an organization